2023
DOI: 10.3390/biom13040609
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Macroion/Growth Factor Assemblies for Medical Applications

Abstract: Growth factors are a class of proteins that play a role in the proliferation (the increase in the number of cells resulting from cell division) and differentiation (when a cell undergoes changes in gene expression becoming a more specific type of cell) of cells. They can have both positive (accelerating the normal healing process) and negative effects (causing cancer) on disease progression and have potential applications in gene therapy and wound healing. However, their short half-life, low stability, and sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 378 publications
(542 reference statements)
1
0
0
Order By: Relevance
“…The results reported in this work showed that chondrocytes were viable and proliferated within the hydrogel, and chondrocytes regained their original morphology and formed aggregates after only 7 days of culture. In accordance with other studies, dedifferentiated chondrocytes started re-expressing chondrogenic markers upon the restoration of a spheroidal shape. , In this study, after 7 days of culture it was possible to observe an increase in the expression of FOXO3A, COL6A1, and ACAN, while the expression of COL1A1 and COL10A1 decreased. On day 7, chondrocytes started to self-assemble, suggesting that they were able to migrate within the hydrogel.…”
Section: Discussionsupporting
confidence: 92%
“…The results reported in this work showed that chondrocytes were viable and proliferated within the hydrogel, and chondrocytes regained their original morphology and formed aggregates after only 7 days of culture. In accordance with other studies, dedifferentiated chondrocytes started re-expressing chondrogenic markers upon the restoration of a spheroidal shape. , In this study, after 7 days of culture it was possible to observe an increase in the expression of FOXO3A, COL6A1, and ACAN, while the expression of COL1A1 and COL10A1 decreased. On day 7, chondrocytes started to self-assemble, suggesting that they were able to migrate within the hydrogel.…”
Section: Discussionsupporting
confidence: 92%